Workforce entry preferences among final-year dental students in Malaysia: public or private sectors? - Mohd Hata, Aimi Aisyah; Jamian, Siti Nur Sarah; Idaham, Nurul Izza; Ab Mumin, Nazirah; Che Musa, Muhd Firdaus; Jaafar, Azlan (IIUM Press, 2026)
Limited job opportunities and restricted advancement in Malaysia’s public dental sector have prompted graduates to explore private sector employment. This may lead to increased workforce mobility and possible instability across the sectors. This study aimed to investigate the workforce preference among the public and private final year undergraduate dental students in Malaysia. A validated questionnaire was disseminated in a cross-sectional study using stratified sampling methods among final year dental students in Malaysia. Chi-square test and multinomial regression were performed to determine factors related to workforce entry preference of the students. In multinomial regression, the public sector was set as the reference group versus the private and both sectors. SPSS version 26 was used for data analysis, with a p-value set less than 0.05. A total of 204 final year dental students’ session 2022/2023 across 13 dental schools in Malaysia were recruited in the study. The majority of respondents have a high preference to work in both public and private oral health services at the same time (public = 58.5% vs private = 43.9%). Multinomial regression analysis showed that public university students had 83% lower odds (OR = 0.17; 95% CI = 0.05, 0.58; p= 0.005) of preference to work in private sectors compared to private university students. In conclusion, the majority of the final year undergraduate dental students preferred to work in both public and private sectors, with more students in the public institution preferring to work in government sectors. To ensure a seamless provision of oral healthcare services, the Ministry of Health Malaysia should come out with an efficient solution in regards with the issues of limited placement of new dental graduates in Malaysia.